Analysis of factors influencing skip lymphatic metastasis in pN2 non-small cell lung cancer - Li, Gui-Long; Zhu, Yong; Zheng, Wei; Guo, Chao-Hui; Chen, Chun (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objective: Although many clinical studies on skip lymphatic metastasis in non-small cell lung cancer have been reported, the risk factors for skip lymphatic metastasis are still controversy and debatable. This study investigated, by multivariate logistic regression analysis, the clinical features of skip metastasis to mediastinal lymph nodes (N2) in non-small cell lung cancer (NSCLC) patients. Methods: We collected the clinicopathological data of 256 pN2-NSCLC patients who underwent lobectomy plus systemic lymph node dissection in Fujian Medical University Union Hospital. The cases in the present study were divided into two groups: skip metastasis (N2 skip+) and non- skip metastasis (N2 skip-). A retrospective analysis of clinical pathological features of two groups was performed. To determine an independent factor, multivariate logistic regression analysis was used to identify possible risk factors. Results: A total of 256 pN2-NSCLC patients were recruited. The analysis results showed that gender, pathologic types, surgery, pleural involvement, smoking history, age, tumor stages, and differentiation were not statistical significant factors impacting on skip metastasis in pN2-NSCLC (P>0.05), whereas tumor size was an independent factor for skip metastasis (P=0.02). Conclusions: The rate of skip lymphatic metastasis increases in pN2-NSCLC patients, in accompany with an increased tumor size.